Building the Profile of Pancasila Students through Adit Sopo Jarwo Animation Series - Aditama, Alif Saifuan; Nurjanah, Ivatul Miftaqul; Prasetyoningsih, Luluk Sri Agus (STAI Miftahul Ula Nganjuk, 2024)
The Pancasila Student Profile is a program within the Merdeka Curriculum aimed at enhancing the quality of education through character education aligned with Pancasila as the state ideology and the foundation of the nation's soul. This study aims to evaluate the implementation of the Pancasila Student Profile within the Merdeka Curriculum. The results indicate that creative content can serve as an effective medium for reinforcing the Pancasila Student Profile. The primary objectives of the Pancasila Student Profile are to uphold the noble values and morals of the nation, prepare students to become inclusive global citizens, achieve social justice, and develop 21st-century competencies. Various methods can be employed to introduce the six Pancasila Learner Profiles. Besides providing direct examples in daily life, the reinforcement of the Pancasila Student Profile can also be achieved through creative content and animated series. One example of an animated series created by Indonesian youth that can be used to strengthen the Pancasila Student Profile is